Contact Pressure and Shear Stress Analysis on Conforming Contact Problem - Haruo NAGATANI; Akitoshi IMOU (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2008)
Two methods to solve a conforming contact problem are proposed. First method is general and can be applicable to the contact case between elastic arbitrary shape bodies. For verification FEA is performed on the convex-concave sphere contact, and the result of this method is well corresponding to the FEA result. However, the accuracy deteriorates when the mesh aspect ratio is extremely large. This phenomenon is caused by the usage of numerical integration for the calculation of influence coefficient. The second method is devised to avoid this problem, while this improved method is applicable only to the case when the contact area can be considered to be on a cylinder surface. By using this method, the contact pressure can be obtained without the deterioration even in the case of edge load occurring between ball bearing race shoulder and ball. The results of the contact pressure and the shear stress that is necessary for bearing life estimation are compared with the FEA result, which showed well correspondence.